1997
DOI: 10.1021/jp962488p
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Diffuse Reflectance Spectroscopy of Supported Chromium Oxide Catalysts:  Kinetics of the Reduction Process with Carbon Monoxide

Abstract: In situ diffuse reflectance spectra of supported chromium oxide catalysts are investigated for the first time at elevated temperatures under controlled reaction conditions using a specially designed diffuse reflection attachment. The obtained results are compared and discussed with those obtained by the classical diffuse reflectance spectroscopy technique. A novel method for studying the reduction kinetics of supported transition metal oxides is proposed. In the case of Cr(VI), the reduction is faster on silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…1). In accordance with the results of detailed studies by Takehira et al (2004) and Bensalem et al (1997), these bands were assigned to O-Cr(VI) electronic charge transfer of chromate species in a tetrahedral conformational structure.…”
Section: Uv-vis Spectrophotometric Titrationsupporting
confidence: 86%
“…1). In accordance with the results of detailed studies by Takehira et al (2004) and Bensalem et al (1997), these bands were assigned to O-Cr(VI) electronic charge transfer of chromate species in a tetrahedral conformational structure.…”
Section: Uv-vis Spectrophotometric Titrationsupporting
confidence: 86%
“…This system has been studied in detail by the groups of Wachs [17][18][19], Iglesia/Bell [20][21][22] and Weckhuysen [23][24][25]. (3) A fibre optics attachment equipped with a high-temper-259 ature probe easily insertable in a catalytic reactor ( Figure 8) [26][27][28].…”
Section: In-situ Instrumentationmentioning
confidence: 99%
“…One can also obtain information about the reduction kinetics of supported chromium oxide catalysts by monitoring the amount of Cr6+ on a catalyst surface during a CO reduction process by using in situ DRS spectroscopy [56,57]. It was found that the amount of Cr6t follows a two-exponential decay for both Cr03/SiO2 and Cr03/Al203 catalysts, but the decay is much faster for a Si02 than for an A1203 support.…”
Section: Catalyst Activationmentioning
confidence: 99%